Boosting the photodynamic therapy of near-infrared AIE-active photosensitizers by precise manipulation of the molecular structure and aggregate-state packing. Issue 30 (25th July 2022) - Ding, Guanyu; Tong, Jialin; Duan, Yingchen; Wang, Shuang; Su, Zhongmin; Shao, Kuizhan; Zhang, Lingyu; Zhu, Daoming; Wen, Li-Li; Li, Yuanyuan; Shan, Guo-Gang
Abstract : A simple molecular engineering strategy to boost photodynamic therapy performance via controlling the molecular structure and solid-packing is demonstrated. Abstract : Organic functional materials have emerged as a promising class of emissive materials with potential application in cancer phototheranostics, whose molecular structures and solid-state packing in the microenvironment play an important role in reactive oxygen species (ROS) generation and the photodynamic therapy (PDT) effect. Clarifying the guidelines to precisely modulate PDT performance from molecular and aggregate levels is desired but remains challenging. In this work, two compounds, TCP-PF6 and TTCP-PF6, with similar skeletons are strategically synthesized, in which a thiophene segment is ingeniously introduced into the molecular backbone of TCP-PF6 to adjust the intrinsic molecular characteristics and packing in the aggregate state. The experimental and theoretical results demonstrate that TTCP-PF6 can form tight packing mode in comparison with TCP-PF6, resulting in efficient cell imaging and enhanced ROS generation ability in vitro and in vivo . The promising features make TTCP-PF6 a superior photosensitizer for PDT treatment against cancer cells by targeting mitochondria. These findings can provide a feasible molecular design for modulating the biological activity and developing photosensitizers with high ROS generation and PDT effect.